A novel approach for segmenting and mapping of local fiber orientation of continuous fiber-reinforced composite laminates based on volumetric images. (March 2020) - Schöttl, Ludwig; Dörr, Dominik; Pinter, Pascal; Weidenmann, Kay André; Elsner, Peter; Kärger, Luise
Abstract: High stiffness and low density of continuous fiber-reinforced polymer (CoFRP) composites lead to increasing importance of this material class in today's lightweight components. One of the most important subgroups of CoFRP composites are thermoplastic UD-tapes. These consist of several unidirectional continuously fiber-reinforced layers which are aligned with different orientations. During the forming process, the initial fiber orientations of the laminate layers change individually. Since the mechanical properties like stiffness or damage behavior are significantly affected by the fiber orientation, methods for determining the fiber orientation distribution are essential to design composite components and validate process simulations. Modern X-ray computed tomography offers the opportunity to obtain high-resolution gray value volumetric images of fiber-reinforced structures. Methods to determine vectors aligned along the local fiber orientation are available in commercial and open-source software. In this paper, we present and compare several segmentation approaches based on layer thickness, fiber orientation angle and degree of fiber isotropy to separate each unidirectional tape layer and to analyze the layers individually. Moreover, we introduce mapping approaches, to transfer local fiber orientation of each tape layer to a discretized surface. The presented approaches can be applied to both plane and curved shell-shaped samples. Finally, the approaches are applied to a carbon fiber-reinforced polyamide 6 (PA6-CF) tape.